Tinjauan Maqosith Syariah Alal Al-Fashi terhadap Seks Long Distance Relationship dalam pembentukan keluarga Harmonis - Nata, Yolies Yongky; Hamidah, Tutik (Neolectura, 2025)
The approach of Maqosith Syariah Alal Al-Fashi towards sex by maturation done by married couples through Video Call because long-distance relationships are allowed because in terms of benefits, the law in maturation is still being debated so that ijtihad is needed in determining the law, maximizing reason as an effort of ijtihad is very important to know and weigh the benefits and harms of maturation done by married couples caused by long-distance relationships, so that by combining the theory of Maqosith Alal Al-Fashi, the theory of Islamic Progressive Law and by using the method of sociological empirical research will be obtained a result that Sex by maturation using Video Call due to long-distance relationships is allowed and has more benefits than harms, and the most important thing from this study shows that sex with maturation through Video call husband and wife will create harmony in the family.